Mini Riset Pembudayaan Pancasila Terhadap Masyarakat - Fiha Fauziah; Jelita Nazwa Utami; Usiono Usiono (LPPM Politeknik Pratama, 2024)
This research employs qualitative methods to explore the role of instilling Pancasila values in Indonesian society, focusing on implementation, comprehension, and its influence on daily life. Interview results with UINSU students demonstrate an awareness of the importance of understanding and applying Pancasila values in creating a unified national identity and upholding social justice. Despite some having implemented Pancasila values, challenges such as a lack of profound understanding and the influence of foreign cultures remain obstacles. Inculcating Pancasila values is pivotal in shaping the character of Indonesian society, yet concerted efforts from various stakeholders are needed to enhance understanding and dissemination across all societal strata.